ACE genetinio žymens vaidmuo vertinant aukšto meistriškumo sportininkus - Anikeviciute, G.; Gineviciene, V. (Sporto Mokslas-Sport Science, 2022)
High-level sports performance is an extremely complex phenotype, and genetic basis is one of its multiple contributory factors. ACE gene produces an angiotensin-converting enzyme, which is the key component of the renin-angiotensin system and involved in various cardiovascular mechanisms. ACE I/D (insertion/deletion, rs4340) polymorphism was one of the first genetic variant to be associated with human physical performance and athletic capacity. Nevertheless, the results of this polymorphism are still inconsistent across studies and populations. Moreover, several investigations suggested the predisposition of the ACE (D allele) with several diseases, e.g. coronary heart diseases, stroke, hypertension and diabetes mellitus. Therefore, the purpose of this case-control association study was to investigate the impact of ACE I/D polymorphism on the adaptation of Lithuanian elite athletes and to determine the relationship between this polymorphism and elite athletes` status. In the present study, ACE I/D polymorphism was investigated in 180 Lithuanian elite athletes representing three functional sports groups (endurance, n = 81; sprint/power, n = 44, and team sports, n = 55), as well as in 255 control samples (non-athletes) from general population of Lithuania. Genomic DNA was extracted from peripheral blood leukocytes. Genotyping was performed using polymerase chain reaction. ACE gene sequence of I/D polymorphism was evaluated by ACE fragment size using 2% agarose gel electrophoresis. Statistical analysis was performed using R Studio 3.4 and SPSS (IBM SPSS v.21). The results of the study showed that genotype frequencies were significantly different between the total Lithuanian elite athlete group and the controls (II/ID/DD: 27.5%, 46.7%, 25.6% vs. 24.7%, 36.9%, 38.4%; p = 0.02). Moreover, sprint/power athlete group (II/ID/DD: 41%; 39%; 20%) had significantly different genotype frequencies compared to controls (p = 0.03). There were a significantly higher ACE I allele frequency in total athletes (51.1%) as well as in sprint/power group (60.2%) compared to controls (43.1%, p < 0.01). Analysis in sports groups by gender showed that ACE II genotype predominates among sprint/power athletes and heterozygous ID genotype prevails among players (team sports). The D allele (56.9%) and DD genotype (38.4%) appeared to be more frequent in controls in comparison to the athletes (D allele 48.9%; DD genotype 25.6%; p < 0.02). The ACE DD genotype was found to reduce the likelihood of becoming a professional athlete (OR = 0.05; 95% CI: 0.362-0.836; p = 0.005), especially in sprint and power sports (OR = 0.18; 95% CI: 0.086-0.375; p < 0.0001) compared to the control group. This case-control association study showed the relationship between ACE I allele (respectively II and ID genotype) and elite athlete status in sprint/power sports. Lithuanian athletes have a lower risk of the D allele (and DD genotype) compared to the non-athletes` controls. The results of the study suggest that the ACE I/D polymorphism significantly contribute to the phenomenal success in sprint and power Lithuanian elite athletes` group.